THE EFFECT OF PRICE FACTORS ON DEMAND FOR WEAVING AT HOME INDUSTRY DUA PELITA BENGKALIS - Delia Desvianti; Seri Wahyuni; Riskiyatul Hasanah; Nina Zakiyah (CV. Adiba Aisha Amira, 2025)
Backgrounds : This research focuses on the home weaving industry, which has an important role in supporting the local economy. The uniqueness and artistic value of woven products is often the main attraction for consumers, but the price factor has now become critical in the developing market dynamics. Objectives : This research aims to investigate the effect of price on demand for woven products in the context of a home industry. Although the industry contributes to cultural preservation and job creation, fluctuations in product demand are a major challenge. This research shows a significant decline in demand for homewoven products in recent years, creating a need for a deeper understanding of the relationship between price and demand. Methods : Using quantitative methods, this research uses sample sales price and sales volume data throughout 2022 to analyze the effect of price on demand. Result and conlusions: The analysis results show that selling price has a significant influence on demand, providing strategic insight for the home weaving industry to increase their competitiveness and economic sustainability.